Descriptions and key to the larvae of the Tasmanian endemic genus Hoplogonus Parry (Coleoptera: Lucanidae), and comparison with the sympatric Lissotes rudis Lea - Richards, Karen; Spencer, Chris P. (Zootaxa, 2014)
The stag beetle (Coleoptera: Lucaindae) genus Hoplogonus Parry is endemic to northeastern Tasmania and contains three recognised species. Descriptions of the imagines have been published previously, but not the larvae. Descriptions of the larvae of the three Hoplogonus species and the sympatric Lissotes rudis Lea (also Lucanidae) are presented and discussed, and a key to aid identification of Hoplogonus larvae is included. The classification of Hoplogonus within the tribe Platycerini is proposed, alongside Lissotes.